Control of Biogenic Amines in Fermented Sausages: Role of Starter Cultures - Latorre-Moratalla, Mariluz; Bover-Cid, Sara; Veciana-Nogués, M.Teresa; Vidal-Carou, M. Carmen (Frontiers in Microbiology, 2012)
Biogenic amines show biological activity and exert undesirable physiological effects when absorbed at high concentrations. Biogenic amines are mainly formed by microbial decarboxylation of amino acids and thus are usually present in a wide range of foods, fermented sausages being one of the major biogenic amine sources. The use of selected starter cultures is one of the best technological measures to control aminogenesis during meat fermentation. Although with variable effectiveness, several works show the ability of some starters to render biogenic amine-free sausages. In this paper, the effect of different starter culture is reviewed and the factors determining their performance discussed.